Educators’ perspective on the use of augmented reality to create STEM learning material - Mokmin, Nur Azlina Mohamed; Ariffin, Ummie Haniffah; Mohd Hamizi, Muhammad Aminuddin Akmal (Journal of ICT in Education, 2022)
Providing learners with educational content based on augmented reality (AR) is a bizarre way to pique their interest in learning. This is because it is predicted that the AR learning material will assist learners to visualise a complex structure, particularly in STEM education. As AR is incorporated into educational settings, it is necessary to take into consideration educators’ perspectives as well. Thus, this study presents educators’ perspectives on using AR for STEM education. In this quantitative study, 30 STEM educator respondents were asked to fill out questionnaires about their perspectives on the use of augmented reality in learning. These perceptions are based on a number of variables which are, perceived usefulness, perceived ease of use, perceives enjoyment, attitude towards its use, and intention of use. Overall, the findings show that majority of STEM educators support the utilization of AR in STEM education. Aside from that, in terms of the intention of use, 87% of the respondents indicated a desire to utilize AR to teach their students. This implies that the use of AR applications is important from the viewpoint of STEM educators. As a result, it is hoped that this study will facilitate future studies to support the significance of using AR in STEM education.